Machiavelli's scientific method: a common understanding of his novelty in the sixteenth century. Issue 8 (17th November 2018) - Almási, Gábor
ABSTRACT: This paper argues that Machiavelli's method, his inductive and comparative use of history and experience for political analysis, and his fashioning of historical-political analysis as 'science', played an important and still unrecognised role in his reception in the sixteenth century. It makes the case that Machiavelli's inductive reasoning and stress on historia and experientia offered a model for scientific method that open-minded sixteenth-century scholars, eager to understand, organise and augment human knowledge ( scientia ), could fit to their own epistemology. By focusing on the question of method—a crucial issue for sixteenth-century contemporaries—the paper offers more than a key to the understanding of Machiavelli's positive reception. It also helps in apprehending the crucial importance of Lucretius to Machiavelli's scholarship; the role of the late Renaissance fascination with historia in his reception; and the breadth of appropriation of his method exactly in the decades when anti-Machiavellianism became official politics all over Europe. These claims are sustained through the cases of Machiavelli's early translators and promulgators; the French legal humanists and historiographers; the Swiss, Italian and French scholars engaging with medicine, Paracelsism and astronomy; the authors of political maxims from all over Europe; and finally Francis Bacon.